Effect of Incorporation of Drumstick Leaf and Jamun Seed Powder on Sensory Quality of Functional Chicken Chips - Kasthuri, S.; Mandal, P. K.; Pal, U. K.; Elanchezhian, N.; Perumal, S. Venkatesa (Journal of Meat Science, 2017)
Natural preservatives can replace the chemical preservatives and their toxic effects contributing health promoting benefits and thereby makes the food functional. This study was undertaken to select the suitable levels of incorporation of drumstick leaf powder (DLP) and Jamun seed powder (JSP) to functional chicken chips (FCC) which was standardized earlier. Different levels (1, 2 and 3%) of drumstick leaf powder (DLP) and (1, 2 and 3%) Jamun seed powders (JSP) were added to the FCC. Functional chicken chips containing 1% DLP and 1% JSP had scores of 6.47 and 6.40 for appearance; 6.47 and 6.37 for flavour; 6.23 and 6.13 for texture; 6.60 and 6.43 for crispiness; 6.53 and 6.27 for acceptance, respectively on 8 point hedonic scale. Sensory scores were significantly (P<0.05)higher for 1% DLP and 1% JSP product among treatments and the scores decreased as the level of incorporation of DLP and JSP increased. Hence, 1% DLP and 1% JSP were selected for the development of functional chicken chips (FCC) as a source of natural antioxidant and natural preservative with added health benefit.